Pharmacokinetic drug–drug interactions between 1,4-dihydropyridine calcium channel blockers and statins: factors determining interaction strength and relevant clinical risk management - Zhou YT; Yu LS; Zeng S; Huang YW; Xu HM; Zhou Q (Dove Medical Press, 2013)
Yi-Ting Zhou,1 Lu-Shan Yu,2 Su Zeng,2 Yu-Wen Huang,1 Hui-Min Xu,1 Quan Zhou11Department of Pharmacy, the Second Affiliated Hospital, School of Medicine, 2Department of Pharmaceutical Analysis and Drug Metabolism, College of Pharmaceutical Sciences, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of ChinaBackground: Coadministration of 1,4-dihydropyridine calcium channel blockers (DHP-CCBs) with statins (or 3-hydroxy-3-methylglutaryl-coenzyme A [HMG-CoA] reductase inhibitors) is common for patients with hypercholesterolemia and hypertension. To reduce the risk of myopathy, in 2011, the US Food and Drug Administration (FDA) Drug Safety Communication set a new dose limitation for simvastatin, for patients taking simvastatin concomitantly with amlodipine. However, there is no such dose limitation for atorvastatin for patients receiving amlodipine. The combination pill formulation of amlodipine/atorvastatin is available on the market. There been no systematic review of the pharmacokinetic drug–drug interaction (DDI) profile of DHP-CCBs with statins, the underlying mechanisms for DDIs of different degree, or the corresponding management of clinical risk.Methods: The relevant literature was identified by performing a PubMed search, covering the period from January 1987 to September 2013. Studies in the field of drug metabolism and pharmacokinetics that described DDIs between DHP-CCB and statin or that directly compared the degree of DDIs associated with cytochrome P450 (CYP)3A4-metabolized statins or DHP-CCBs were included. The full text of each article was critically reviewed, and data interpretation was performed.Results: There were three circumstances related to pharmacokinetic DDIs in the combined use of DHP-CCB and statin: 1) statin is comedicated as the precipitant drug (pravastatin–nimodipine and lovastatin–nicardipine); 2) statin is comedicated as the object drug (isradipine–lovastatin, lacidipine–simvastatin, amlodipine–simvastatin, benidipine-simvastatin, azelnidipine–simvastatin, lercanidipine–simvastatin, and amlodipine–atorvastatin); and 3) mutual interactions (lercanidipine–fluvastatin). Simvastatin has an extensive first-pass effect in the intestinal wall, whereas atorvastatin has a smaller intestinal first-pass effect. The interaction with simvastatin seems mainly driven by CYP3A4 inhibition at the intestinal level, whereas the interaction with atorvastatin is more due to hepatic CYP3A4 inhibition. The interaction of CYP3A4 inhibitor with simvastatin has been more pronounced compared with atorvastatin. From the current data, atorvastatin seems to be a safer CYP3A4-statin for comedication with DHP-CCB. There is no convincing evidence that amlodipine is an unusual DHP-CCB, either as a precipitant drug or as an object drug, from the perspective of CYP3A4-mediated drug metabolism. Amlodipine may have interactions with CYP3A5 in addition to CYP3A4, which may explain its particular characteristics in comparison with other DHP-CCBs. The degree of DDIs between the DHP-CCB and statin and the clinical outcome depends on many factors, such as the kind of statin, physicochemical proprieties of the DHP-CCB, the dose of either the precipitant drug or the object drug, the sex of the patient (eg, isradipine–lovastatin), route of drug administration (eg, oral versus intravenous nicardipine–lovastatin), the administration schedule (eg, nonconcurrent dosing method versus concurrent dosing method), and the pharmacogenetic status (eg, CYP3A5-nonexpressers versus CYP3A5-expressers).Conclusion: Clinical professionals should enhance risk management regarding the combination use of two classes of drugs by increasing their awareness of the potential changes in therapeutic efficacy and adverse drug reactions, by rationally prescribing alternatives, by paying attention to dose adjustment and the administration schedule, and by review of the appropriateness of physician orders. Further study is needed – the DDIs between DHP-CCBs and statins have not all been studied in humans, from either a pharmacokinetic or a clinical perspective; also, the strength of the different pharmacokinetic interactions of DHP-CCBs with statins should be addressed by systematic investigations.Keywords: CYP3A4, 1,4-dihydropyridine, drug–drug interactions, HMG-CoA reductase inhibitors, myopathy, polypharmacy, physicochemical phenomena, prescription auditing